KELUHAN NYERI PUNGGUNG BAWAH DI KALANGAN PEKERJA KERAJINAN TASBIH - Indrayani, Reny; Wati, Dwi Martiana; Agustini, Aisa Tri (Fakultas Kesehatan Masyarakat, Universitas Jember, 2019)
Low back pain (LBP) is usually perceived by individuals that mostly do static activities, including craft workers. The daily activities are predominantly by sitting on the floor while doing crafting for about eight hours a day. Consequently, prevention strategies should be promoted in order to avoid more severe situation. This research aims to identify several presumable aspects that may lead to an increase in possibility of getting LBP. A descriptive approach was applied in this research while involving 22 craft workers from two craft industries that are located in Tutul and Balung Kulon village, Balung sub-district, Jember, as subjects research. The result has pointed out that many female workers perceived severe LBP. This could get more severe along with an increase in age and body mass index as well as abdominal circumference. For history of spine trauma, workers who never had a such traumatic history appeared to get severe LBP. Therefore, this findings suggest that encouraging awareness towards early symptoms of LBP as well as doing back exercise, which is designed to alleviate low back pain, routinely will be the effective solutions to reduce severity in LBP.